Islamic approach in managing stress within study on perceived stress score & academic performance in continuous assessment among third year pharmacy students - Soe, May Khin Soe; Baharudin, Mohamad Sharul Fahmi; Uzir, Bisha Fathamah (2016)
Introduction: Professional education such as Pharmacy Programme basically demands massive hard work and challenges for students due to various assessment methods and heavy co-curricular activities. Objectives: In order to observe how students approach Islamic way to manage the stress, we studied this retrospective study after conducting cross sectional exploratory study that detected the relationship between the PSS and their academic achievement throughout the semester. Method: Total 114 third year students including 29 male and 85 female participated. Their marks obtained from 4 quizzes and respective PSS were recorded periodically and analysed descriptively. We provided some questionnaires to check their psychological coping mechanisms and observed how they apply the Islamic approach as one of the key components of managing stress. Result: The PSS score for overall male and female is highest in the second quiz which was 38.99 ± 6.60 compared to first and third/fourth quizzes which were 38.90 ± 5.60 and 38.10 ± 7.18 respectively. Mean marks students achieved were 7.61±1.25 in Quiz 1; 4.97±1.41 in quiz 2; 6.04±1.77 in quiz 3; 5.71 ±1.32 in 4 respectively. There were 61 (53.5%) students including 22 male (75% of male) and 40 female (47.05% of female) who freely commented on the way of coping stress by Islamic ways such as Tawakal and suitable du’a before answering the quiz. The lowest PSS value (28.33±7.76) was observed for 8 (7%) female students who expressed in Islamic way that they studied the course to obtain the knowledge for the sake of hereafter. They all passed and obtained good score with mean value of 26.19±4.27. The highest PSS on overall was 42.43± 8.12. Those who in that value were not displayed any comment regarding on how to overcome their stressful condition in Islamic way. Conclusion: Hence, proper stress management is a very pivotal element for students to perform well academically and spiritually.